The role of foreign technologies and R&D in innovation processes within catching-up CEE countries - Prokop, Viktor; Stejskal, Jan; Klimova, Viktorie; Zitek, Vladimir (Public Library of Science, 2021)
Prior research showed that there is a growing consensus among researchers, which point out a key role of external knowledge sources such as external R&D and technologies in enhancing firms ' innovation. However, firms ' from catching-up Central and Eastern European (CEE) countries have already shown in the past that their innovation models differ from those applied, for example, in Western Europe. This study therefore introduces a novel two-staged model combining artificial neural networks and random forests to reveal the importance of internal and external factors influencing firms ' innovation performance in the case of 3,361 firms from six catching-up CEE countries (Czech Republic, Slovakia, Poland, Estonia, Latvia and Lithuania), by using the World Banks ' Enterprise Survey data from 2019. We confirm the hypothesis that innovators in the catching-up CEE countries depend more on internal knowledge sources and, moreover, that participation in the firms groups represents an important factor of firms ' innovation. Surprisingly, we reject the hypothesis that foreign technologies are a crucial source of external knowledge. This study contributes to the theories of open innovation and absorptive capacity in the context of selected CEE countries and provides several practical implications for firms.
Role zahraničních technologií a R&D v inovačních procesech v zemích CEE
Keywords: artificial neural-networks; absorptive-capacity; logistic-regression; knowledge spillovers; sensitivity-analysis; radical innovation; empirical-analysis; random forests; black-box; industry; umělé neuronové sítě; absorpční kapacita; logistická regrese; přelévání znalostí; analýza citlivosti; radikální inovace; empirická analýza; náhodné lesy; černá skříňka; odvětví